The robber [videorecording (DVD)] - Heisenberg, Benjamin; Prinz, Martin, 1973-; Lust, Andreas, 1967-; Weisz, Franziska, 1980-; Schleinzer, Markus, 1971- (Kino International, 2011)
Based on the true story of Johann Kastenberger, who was a champion marathoner who lead a double life as a serial bank robber, sprinting between fixes, and away from police cavalcades, as many as three times a day. A lean, visceral study of pathological compulsion from Austrian director Benjamin Heisenberg, featuring a riveting central performance by Andreas Lust.